Clinicopathological Profile and Disease-Free Survival in Stage I-II Endometrial Cancer at Cipto Mangunkusumo Hospital - Muhammad Rizkinov Jumsa; Tricia Dewi Anggraeni; Tantri Hellyanti; Kartiwa Hadi Nuryanto (Faculty of Medicine, Hasanuddin University., 2025)
Introduction: This study aimed to describe the clinicopathological profile and evaluate the disease-free survival (DFS) of patients with FIGO 2009 stage I–II endometrioid endometrial cancer, and to determine the prognostic value of key factors, emphasizing lymphovascular space invasion (LVSI) and tumor grade. Methods: A retrospective cohort of 111 patients treated between January 2017 and December 2022 was analyzed. Variables included age, menopausal status, BMI, depth of myometrial invasion, LVSI, and tumor grade. Survival was estimated using the Kaplan–Meier method; associations were assessed with Fisher’s exact test, and independent prognostic factors were identified using multivariate Cox regression analysis Results: The median follow-up for the 111 patients was 32 months. Most were stage IB (42.4%), aged 45–60 years (46.8%), postmenopausal (73%), and obese (63%). Stage-specific DFS rates were: Stage IA – 94.6% (1-year), 87.8% (2-year), 87.8% (3-year); Stage IB – 93.6% (1-year), 91.0% (2-year), 91.0% (3-year); Stage II – 92.6% (1-year), 88.9% (2-year), 88.9% (3-year). LVSI positivity (15.3%) and high tumor grade emerged as the strongest prognostic factors. Multivariate analysis confirmed LVSI as an independent predictor across all stages, with hazard ratios ranging from 3.85 in stage IA to 4.25 in stage IB and 12.5 in stage II (p<0.05). In stage II, LVSI-positive patients showed a 57.1% 3-year DFS versus 100% in LVSI-negative patients. Conclusions: LVSI and tumor grade are independent, interrelated prognostic markers in early-stage endometrial carcinoma. Their integration into risk stratification refines adjuvant therapy guidance. Implementation requires standardized pathological reporting and efficient referral systems to improve long-term surveillance adherence.